Activating Adenosine Monophosphate–Activated Protein Kinase Mediates Fibroblast Growth Factor 1 Protection From Nonalcoholic Fatty Liver Disease in Mice. Issue 6 (18th June 2021) - Lin, Qian; Huang, Zhifeng; Cai, Genxiang; Fan, Xia; Yan, Xiaoqing; Liu, Zhengshuai; Zhao, Zehua; Li, Jingya; Li, Jia; Shi, Hongxue; Kong, Maiying; Zheng, Ming‐Hua; et al.
Abstract : Background and Aims: Fibroblast growth factor (FGF) 1 demonstrated protection against nonalcoholic fatty liver disease (NAFLD) in type 2 diabetic and obese mice by an uncertain mechanism. This study investigated the therapeutic activity and mechanism of a nonmitogenic FGF1 variant carrying 3 substitutions of heparin‐binding sites (FGF1 △HBS ) against NAFLD. Approach and Results: FGF1 △HBS administration was effective in 9‐month‐old diabetic mice carrying a homozygous mutation in the leptin receptor gene ( db/db ) with NAFLD; liver weight, lipid deposition, and inflammation declined and liver injury decreased. FGF1 △HBS reduced oxidative stress by stimulating nuclear translocation of nuclear erythroid 2 p45‐related factor 2 (Nrf2) and elevation of antioxidant protein expression. FGF1 △HBS also inhibited activity and/or expression of lipogenic genes, coincident with phosphorylation of adenosine monophosphate–activated protein kinase (AMPK) and its substrates. Mechanistic studies on palmitate exposed hepatic cells demonstrated that NAFLD‐like oxidative damage and lipid accumulation could be reversed by FGF1 △HBS . In palmitate‐treated hepatic cells, small interfering RNA (siRNA) knockdown of Nrf2 abolished only FGF1 △HBS antioxidative actions but not improvement of lipid metabolism. In contrast, AMPK inhibition by pharmacological agent or siRNA abolished FGF1 △HBS benefits on both oxidative stress and lipid metabolism that were FGF receptor (FGFR) 4 dependent. Further support of these in vitro findings is that liver‐specific AMPK knockout abolished therapeutic effects of FGF1 △HBS against high‐fat/high‐sucrose diet–induced hepatic steatosis. Moreover, FGF1 △HBS improved high‐fat/high‐cholesterol diet–induced steatohepatitis and fibrosis in apolipoprotein E knockout mice. Conclusions: These findings indicate that FGF1 △HBS is effective for preventing and reversing liver steatosis and steatohepatitis and acts by activation of AMPK through hepatocyte FGFR4.